Envelhecência enquanto experiência: sobre o curso para formação de professores sobre envelhecimento na cidade de São Carlos/SP - Denari, Giulianna Bueno (Universidade Federal de São Carlos, 2025)
This study aims to document the development and implementation experience of the EnvelheCiência course, an initiative focused on teacher education regarding aging and combating ageism. Conducted in schools in São Carlos/SP, Brazil, the course sought to integrate biological and social knowledge into pedagogical practices, emphasizing the importance of addressing this theme in educational contexts. The methodology employed involved an experiential account of the course's formulation and execution in a pilot format, delivered through in-person sessions. The findings highlight the need to incorporate aging-related content into school curricula and develop specific teaching materials, while also demonstrating the course's educational potential by engaging teachers with a universally relevant subject. The experience revealed how schools can become crucial spaces for promoting more inclusive and respectful perspectives on aging, thereby contributing to a more equitable and welcoming society for all ages. Additionally, it underscored educators' workload challenges and suggested that hybrid teaching models combining in-person and asynchronous elements may enhance participant engagement. As an educational practice, the experience profoundly influenced the researcher, demonstrating the importance of continuing education, active methodologies, and reflective processes in educators' professional development
Aging as experience: about the teacher training course on aging in the city of São Carlos/SP
Keywords: Formação continuada; Envelhecimento; Relato de experiência; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM